2016
DOI: 10.1162/jocn_a_00888
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Frontal and Parietal Cortex in Proactive and Reactive Inhibitory Control: A Transcranial Direct Current Stimulation Study

Abstract: Mounting evidence suggests that response inhibition involves both proactive and reactive inhibitory control, yet its underlying neural mechanisms remain elusive. In particular, the roles of the right inferior frontal gyrus (IFG) and inferior parietal lobe (IPL) in proactive and reactive inhibitory control are still under debate. This study aimed at examining the causal role of the right IFG and IPL in proactive and reactive inhibitory control, using transcranial direct current stimulation (tDCS) and the stop s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 83 publications
(128 reference statements)
6
43
2
Order By: Relevance
“…tDCS neuromodulation of various targets has been increasingly applied in treatment research (e.g., to relieve major depression Meron et al, 2015), but it has also been used for experimental manipulation of neural networks to enhance or diminish specific cognitive functions or symptoms, including impulsivity. Anodal tDCS applied to the rIFG appears to reduce behavioral impulsivity (Cai et al, 2016; Cunillera et al, 2014; Ditye et al, 2012; Stramaccia et al, 2015), whereas anodal tDCS to the left OFC has been found to lead to a reduction in cognitive impulsivity (Ouellet et al, 2015). If behavioral and cognitive impulsivity are implicated in short-term risk for self-injurious thoughts and behaviors, tDCS may therefore have potential to become a new protocol for addressing these clinical outcomes, through targeting the respective underlying neural circuitry of these facets of impulsivity.…”
Section: Discussionmentioning
confidence: 96%
“…tDCS neuromodulation of various targets has been increasingly applied in treatment research (e.g., to relieve major depression Meron et al, 2015), but it has also been used for experimental manipulation of neural networks to enhance or diminish specific cognitive functions or symptoms, including impulsivity. Anodal tDCS applied to the rIFG appears to reduce behavioral impulsivity (Cai et al, 2016; Cunillera et al, 2014; Ditye et al, 2012; Stramaccia et al, 2015), whereas anodal tDCS to the left OFC has been found to lead to a reduction in cognitive impulsivity (Ouellet et al, 2015). If behavioral and cognitive impulsivity are implicated in short-term risk for self-injurious thoughts and behaviors, tDCS may therefore have potential to become a new protocol for addressing these clinical outcomes, through targeting the respective underlying neural circuitry of these facets of impulsivity.…”
Section: Discussionmentioning
confidence: 96%
“…However, the lack of significant changes in the SSRT suggests no effects on reactive inhibition. Although there have been positive results in tDCS studies using the SST in a healthy population targeting other areas like the right inferior frontal gyrus [37][38][39][40][41][42] , previous tDCS studies with ADHD patients using the SST and targeting the DLPFC have also found a lack of significant effects on the SSRT and accuracy 28,43 . These results support the formulation of inhibitory control and impulsivity as complex multimodal processes with subdomain specificity (e.g.…”
Section: Flanker Taskmentioning
confidence: 99%
“…As mentioned above, such work is important for its potential to lead to the identification of potential targets for intervention. Within this context, the right inferior frontal gyrus (rIFG) may be a region of particular interest, as it has been observed in several studies to be responsive to anodal tDCS (Cai et al, 2016; Cunillera et al, 2014; Ditye et al, 2012; Stramaccia et al, 2015). The rIFG has been found to be involved in cognitive interference resolution (Berman et al, 2011).…”
Section: Repetitive Nssi As a Behavior Requiring Reduced Effortmentioning
confidence: 99%